The Merck Manual Home Health Handbook - Porter, Robert S., 1950-; Kaplan, Justin L.; Homeier, Barbara P.; Albert, Richard K. (Whitehouse Station, NJ : Merck Research Laboratories, 2009)
From the Publisher: This comprehensive medical resource, The Merck Manual-Third Home Edition, extensively covers health care for newborns, the elderly, and everyone in between. The new Third Home Edition provides the same authoritative information doctors have relied on in The Merck Manual, for more than a century, in easy-to-understand, everyday language. Previous editions have sold more than 3 million copies. Written by more than 200 internationally respected medical experts, this new edition of the world's bestselling reference presents in-depth information for medical situations, including: Aging, Gynecological Disorders, Heart disease, Digestive disorders, Cancer, Nutrition problems, AIDS, Hormonal problems, Infections and immunizations, Neurological Disorders, Pediatric Disorders, Men's, women's and children's health issues, Mental health disorders, Accidents and injuries, Care for the dying,and much more.
13: Blood Disorders -- 153: Biology of blood -- 154: Symptoms and diagnosis of blood disorders -- 155: Blood transfusion -- 156: Anemia -- 157: Bleeding and clotting disorders -- 158: White blood cell disorders -- 159: Plasma cell disorders -- 160: Leukemias -- 161: Lymphomas -- 162: Myeloproliferative disorders -- 163: Spleen disorders -- 14: Cancer -- 164: Overview of cancer -- 165: Symptoms and diagnosis of cancer -- 166: Prevention and treatment of cancer -- 15: Immune Disorders -- 167: Biology of the immune system -- 168: Immunodeficiency disorders -- 169: Allergic reactions -- 170: Autoimmune disorders -- 171: Transplantation -- 16: Infections -- 172: Biology of infectious disease -- 173: Immunization -- 174: Bacterial infections -- 175: Bacteremia, sepsis, and septic shock -- 176: Antibiotics -- 177: Tuberculosis -- 178: Leprosy -- 179: Rickettsial and related infections -- 180: Parasitic infections -- 181: Fungal infections -- 182: Viral infections -- 183: Human immunodeficiency virus infection -- 184: Sexually transmitted diseases -- 17: Skin Disorders -- 185: Biology of the skin -- 186: Diagnosis and treatment of skin disorders -- 187: Itching and noninfectious rashes -- 188: Acne -- 189: Pressure sores -- 190: Sweating disorders -- 191: Hair disorders -- 192: Pigment disorders -- 193: Blistering diseases -- 194: Parasitic skin infections -- 195: Bacterial skin infections -- 196: Fungal skin infections -- 197: Viral skin infections -- 198: Sunlight and skin damage -- 199: Noncancerous skin growths -- 200: Skin cancers -- 201: Nail disorders -- 18: Mouth And Dental Disorders -- 202: Biology of the mouth -- 203: Lip and tongue disorders -- 204: Salivary gland disorders -- 205: Mouth sores -- 206: Mouth growths -- 207: Tooth disorders -- 208: Periodontal diseases -- 209: Temporomandibular disorders -- 210: Urgent dental problems -- 19: Ear, Nose, And Throat Disorders -- 211: Biology of the ears, nose, and throat -- 212: Hearing loss and deafness -- 213: Outer ear disorders -- 214: Middle and inner ear disorders -- 215: Nose, sinus, and taste disorders -- 216: Throat disorders -- 217: Nose and throat cancers -- 20: Eye Disorders -- 218: Biology of the eyes -- 219: Symptoms and diagnosis of eye disorders -- 220: Refractive disorders -- 221: Injuries of the eye -- 222: Eyelid and tearing disorders -- 223: Conjunctival and scleral disorders -- 224: Corneal disorders -- 225: Cataract -- 226: Uveitis -- 227: Glaucoma -- 228: Retinal disorders -- 229: Optic nerve disorders -- 230: Eye socket disorders -- 21: Men's Health Issues -- 231: Male reproductive system -- 232: Penile and testicular disorders -- 233: Prostate disorders -- 234: Sexual dysfunction in men -- 22: Women's Health Issues -- 235: Female reproductive system -- 236: Symptoms and diagnosis of gynecologic disorders -- 237: Sexual dysfunction in women -- 238: Menopause -- 239: Menstrual disorders and abnormal vaginal bleeding -- 240: Endometriosis -- 241: Fibroids -- 242: Vaginal infections -- 243: Pelvic inflammatory disease -- 244: Pelvic floor disorders -- 245: Breast disorders -- 246: Noncancerous gynecologic abnormalities -- 247: Cancers of the female reproductive system -- 248: Violence against women -- 249: Infertility -- 250: Family planning -- 251: Detection of genetic disorders -- 252: Normal pregnancy -- 253: High-risk pregnancy -- 254: Pregnancy and complicated by disease -- 255: Pregnancy and drug use -- 256: Complications of pregnancy -- 257: Normal labor and delivery -- 258: Complications of labor and delivery -- 259: Postdelivery period -- 23: Children's Health Issues -- 260: Newborns and infants -- 261: Problems in newborns -- 262: Birth defects -- 263: Chromosomal and genetic abnormalities -- 264: Problems in infants and very young children -- 265: Preschool and school-aged children -- 266: Behavioral and developmental problems in young children -- 267: Adolescents -- 268: Problems in adolescents -- 269: Bacterial infections -- 270: Viral infections -- 271: Respiratory disorders -- 272: Cystic fibrosis -- 273: Digestive disorders -- 274: Neurologic disorders -- 275: Ear, nose, and throat disorders -- 276: Eye disorders -- 277: Bone disorders -- 278: Hereditary connective tissue disorders -- 279: Juvenile idiopathic arthritis -- 280: Diabetes mellitus -- 281: Hereditary metabolic disorders -- 282: Hereditary periodic fever syndromes -- 283: Childhood cancers -- 284: Learning and developmental disorders -- 285: Cerebral palsy -- 286: Mental retardation/intellectual disability -- 287: Mental health disorders -- 288: Social issues affecting children and their families -- 289: Child neglect and abuse -- 24: Older People's Health Issues -- 290: Aging body -- 291: Aging and drugs --292: Provision of care -- 293: Health care coverage for older people -- 294: Long-term care -- 295: Coping with changes related to aging -- 296: Driving -- 297: Falls -- 298: Elder mistreatment -- 25: Injuries And Poisoning -- 299: First aid -- 300: Burns -- 301: Fractures -- 302: Sports injuries -- 303: Heat disorders -- 304: Cold injuries -- 305: Radiation injury -- 306: Electrical and lightning injuries -- 307: Drowning -- 308: Diving and compressed air injuries -- 309: Altitude illness -- 310: Poisoning -- 311: Bites and stings -- 26: Special Subjects -- 312: Science of medicine and clinical trials -- 313: Medical decision making -- 314: Common imaging tests -- 315: Hospital care -- 316: Surgery -- 317: Complementary and alternative medicine -- 318: Medicinal herbs and nutraceuticals -- 319: Drug use and abuse -- 320: Travel and health -- 321: Amyloidosis -- 322: Disorders of unknown cause -- Appendixes -- 1: Weights and measures -- 2: Common medical tests -- 3: Drug names : generic and trade -- 4: Resources for help and information -- Index.
Previously published as: The Merck manual of medical information, Home ed.
Includes index.
Medicine and Health
Keywords: Medicine, Popular; Medicine, Popular -- Handbooks, manuals, etc; Self-care, Health -- Handbooks, manuals, etc; Diseases; Health; Disease -- Popular Works; Health Behavior -- Popular Works; Medicine -- Popular Works